2023
DOI: 10.3390/microorganisms11030558
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Novel Tellurium Nanorods by Gayadomonas sp. TNPM15 Isolated from Mangrove Sediments and Assessment of Their Impact on Spore Germination and Ultrastructure of Phytopathogenic Fungi

Abstract: The biosynthesis of nanoparticles using green technology is emerging as a cost-efficient, eco-friendly and risk-free strategy in nanotechnology. Recently, tellurium nanoparticles (TeNPs) have attracted growing attention due to their unique properties in biomedicine, electronics, and other industrial applications. The current investigation addresses the green synthesis of TeNPs using a newly isolated mangrove-associated bacterium, Gayadomonas sp. TNPM15, and their impact on the phytopathogenic fungi Fusarium ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 94 publications
0
17
0
Order By: Relevance
“…Singh et al 42 found that 15 isolates have antibacterial activity against Gram‐positive bacteria and MDR bacteria by the perpendicular streak method. Ghany et al, 38 discovered that actinomycete‐mediated silver nanoparticles could disrupts the life cycle of mycotoxigenic fungi, inhibiting conidial germination and compromising membrane integrity, leading to reduced aflatoxin and ochratoxin A production. The metabolite production by submerged state fermentation techniques shows good results in antimicrobial activity 43 against pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Singh et al 42 found that 15 isolates have antibacterial activity against Gram‐positive bacteria and MDR bacteria by the perpendicular streak method. Ghany et al, 38 discovered that actinomycete‐mediated silver nanoparticles could disrupts the life cycle of mycotoxigenic fungi, inhibiting conidial germination and compromising membrane integrity, leading to reduced aflatoxin and ochratoxin A production. The metabolite production by submerged state fermentation techniques shows good results in antimicrobial activity 43 against pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The isolates LA2(R) M. proteolyticum and LA2(O) S. rochei were inoculated in a 500 mL flask containing 100 mL of ISP‐2 medium (g/L): yeast extract, 4.0; malt extract, 10.0; dextrose, 4.0; agar, 20.0; distilled water, 1000 mL; and pH, 7.3. The flasks with inoculated strains were incubated for 5–7 days at 200 rpm in a rotary shaker 38 . The cultures were centrifuged at 10,000 rpm after the growth, and its supernatant was used for future experimentations 39 …”
Section: Methodsmentioning
confidence: 99%
“…Thus, many authors did not try to. However, to date, many such (nano)formulations have been developed using microalgal [10,47], bacterial [48,49], fungal [50], plant [51,52], and other isolates. A slightly more accurate method applies, at least, partially purified proteins [53,54] and pure polypeptides [55] for the green synthesis of NPs.…”
Section: Green Synthesis Of Nps and Its Influence On Mechanisms Of Th...mentioning
confidence: 99%
“…Thus, different metal NPs can be synthesized via the green route (Table 2 [10,[47][48][49][50][51][52][53][54][55]). For example, the application of Ag led to the profound antibacterial activity of obtained formulations [48,52], thus giving additional functionality and opening an opportunity to treat multi-microbial associations.…”
Section: Green Synthesis Of Nps and Its Influence On Mechanisms Of Th...mentioning
confidence: 99%
See 1 more Smart Citation